Poverty alleviation and tropical forests: what scope for synergies? (extract) - Wunder, Sven (Food and Agriculture Organization of the United Nations, 2007)
This is an exptract of a paper explores the "state of the art" of the two-way causal links between poverty alleviation and natural tropical forests. Microimpacts of rising poverty can increase or slow forest loss. At the macrolevel, poverty also has an ambiguous effect, but it is probable that higher income stimulates forest loss by raising demand for agricultural land. The second question is what potential forest-led development has to alleviate a country's poverty, in terms of producer benefits, consumer benefits and economy-wide employment. Natural forests widely serve as "safety nets" for the rural poor, but it proves difficult to raise producer benefits significantly. Urban consumer benefits from forest, an important target for pro-poor agricultural innovation, are limited and seldom favor the poor. Absorption of (poor) unskilled labor is low in forestry, which tends to be capital-intensive. Natural forets may thus lack comparative advantage for poverty alleviation. There are few "win-win" synergies between natural forests and national poverty reduction, which may help to explain why the loss of tropical forests is ongoing. This may have important implications for our understanding of "sustainable forest development" and for the design of both conservation and poverty-alleviation strategies.